The Role of Competence, Discipline, and Integrity in the Context of Organizational Culture and Employee Empowerment in Improving Employee Performance : Systematic Literature Review - Murdiono, Jatmiko; Suhud, Usep; Wibowo, Agus (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The role of employees greatly determines the success of an organizational or company goal. Therefore, this study aims to analyze factors that affect employee performance ranging from factors of competence, discipline, and integrity as direct influences. Then organizational culture and employee empowerment as direct and indirect influences that affect employee performance through data collection with literature surveys which are then analyzed and described. So it is known that this study found that competence, discipline, integrity on employee performance and organizational culture as well as employee empowerment have a direct and indirect influence on employee performance. This research has the opportunity to be investigated further for future research, by developing empirical models of employee performance using other factors.